Geek entrepreneurs: the social network, Iron Man and the reconfiguration of hegemonic masculinity. Issue 3 (3rd April 2023) - Mendick, Heather; Ottemo, Andreas; Berge, Maria; Silfver, Eva
ABSTRACT: In this paper, we argue that the geek entrepreneur is a new hegemonic masculine formation superseding the macho formation exemplified by John Wayne and the global business masculinity proposed as hegemonic by Connell and Messerschmidt more recently. This formation fuses the technological genius and suffering of geekiness with the disruption and innovation of entrepreneurialism. It is the masculinity of the geek entrepreneur that today legitimates both male domination and capitalism. We construct this argument through looking in detail at two cinematic representations of the geek entrepreneur: Mark Zuckerberg in The Social Network and Tony Stark in Iron Man . We hope to open up a debate about how gendered discursive formations have changed since the 1980s, what masculinity is now hegemonic, and how this can illuminate gender and other power relations.